Analisis Kualitas Pembinaan dan Pengembangan Jiwa Kewirausahaan di Kalangan Mahasiswa (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Universitas Jenderal Soedirman Purwokerto) - Untung Kumorohadi; Nurhayati Indiyastuti (Jurnal Ekonomi Bisnis dan Akuntansi (JEBA), 2011)
ABSTRACT The main purposes of this study are to evaluate the quality of the entrepreneurship subject and to analyze entrepreneurship program development in Economic Faculty to stimulate and encourage student’s entrepreneurship spirit.The result from 100 sample students in five department of Economic Faculty, shown that  they are quite satisfied with the quality of the entrepreneurship subject, but there are still some indicator should be improved to make the quality of the entrepreneurship subject better. Economic faculty of Jenderal Soedirman University Purwokerto have already developed some programs to increase  the entrepreneurship spirit for their students, for example encourage their students to be the participant of the PKM, and PMW programs and give support for the seminars and discussion that presented by UKM Bursa, HMJM, HMA, and HMPS.The result of this study is expected to be inputs for faculty and university and especially for the policy makers so that can stimulate and encourage entrepreneurship spirit in Jenderal Soedirman University students. Keywords;  quality of the enterpreneurship subject, entrepreneurship spirit